2009
DOI: 10.2174/156652409788167087
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and Radiation Therapy: Past History, Ongoing Research, and Future Promise

Abstract: Tumor hypoxia influences the outcome of treatment with radiotherapy, chemotherapy and even surgery, not only for the treatment of large bulky tumors with extensive necrosis, but also in the treatment of very small primary tumors and recurrences, micrometastases, and surgical margins with microscopic tumor involvement. Because hypoxic tumor cells are resistant to radiation and to many anticancer drugs, many approaches to circumventing the therapeutic resistance induced by hypoxia have been examined in laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
337
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(356 citation statements)
references
References 129 publications
(178 reference statements)
2
337
0
3
Order By: Relevance
“…As an indicator of tumour resistance PATIENT-SPECIFIC VIRTUAL FMISO-PET 39 to many forms of treatment (Rockwell et al, 2009), hypoxia is an important and defining characteristic of GBM, and the impact a patient-specific predictive model could have on treatment planning is immense. We have made every effort to apply our model to clinical situations and maximize their utility in such circumstances.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an indicator of tumour resistance PATIENT-SPECIFIC VIRTUAL FMISO-PET 39 to many forms of treatment (Rockwell et al, 2009), hypoxia is an important and defining characteristic of GBM, and the impact a patient-specific predictive model could have on treatment planning is immense. We have made every effort to apply our model to clinical situations and maximize their utility in such circumstances.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, hypoxia is an indicator of tumour resistance to many forms of treatment (Rockwell et al, 2009). An accurate and predictive map of tumour hypoxia may allow clinicians to use more quantitative and systematic methods, compared to the relatively qualitative techniques currently used in treating patients, to improve patient survival and quality of life.…”
Section: Clinical Implications For Virtual Fmiso-pet Imagesmentioning
confidence: 99%
“…An enhancement of the radiation damage 2 can be triggered directly in the DNA of tumour cells by selective incorporation of DNA base analogues, 3 for example, or indirectly, via radiation induced secondary processes leading to the release of free electrons 4 and reactive species, as well as oxygen and "oxygen mimetic" compounds. 5 Indeed hypoxia, which is a consequence of the inefficient vascularisation of some tumours, favours the metabolism and growth of tumour cells and makes them more resistant to radiotherapy 6 than the ones in a normally oxygenated environment. In this respect oxygen is a potent radiosensitiser.…”
mentioning
confidence: 99%
“…In this respect oxygen is a potent radiosensitiser. 5 Nitric oxide has long been recognized for its effects in tumour reoxygenation [7][8][9] and has been considered an even more efficient radiosensitiser than oxygen itself [see, for example, Ref. 10 and references therein].…”
mentioning
confidence: 99%
“…Her work is focused on studying the unphysiological microenvironments of cells within solid tumors, its influence on the biology of tumor cells and of the stromal elements within solid tumors. 70 She showed that the microenvironmental inadequacies within solid tumors alter the proliferation patterns of the cells, the metabolic pathways used by the cells, the ability of the cells to tolerate stress, DNA damage, and other injuries, and the response of the cells to radiation and antineoplastic drugs. 71,72 Rockwell studies their implication on the development and progression of solid tumors.…”
mentioning
confidence: 99%